From head to toe - Carle, Eric. ([New York] : HarperCollins, 1997)
Encourages the reader to exercise by following the movements of various animals; presented in a question and answer format.
80
Accelerated Reader AR
Keywords: Exercise -- Juvenile literature; Physical fitness -- Juvenile literature; Exercise; Physical fitness